Gender Difference in Early Occupational Attainment: The Roles of Study Field, Gender Norms, and Gender Attitudes. Issue 3 (3rd July 2018) - He, Guangye; Zhou, Muzhi
Abstract: Drawing data from the Beijing College Student Panel Survey, this article examines how study fields would influence gender disparities in early occupational attainment in China. Results from multinomial logistic regression show that women are more likely than men to become office clerks, a typically female-dominated occupation. Gender disparities in professional/technical occupations are largely attributed to women's underrepresentation in science and engineering fields. As to managerial/marketing occupations, after controlling for study field, gender disparity in attaining these jobs grows even larger. Innovatively constructing a hypothetical scenario, we further examined probable career outcomes if women were as likely as men to enter the specific study field. Our results suggest that, despite pervasive influence of gender norms, egalitarian gender attitudes at job entry can partially moderate women's disadvantage in entering male-dominated occupations. Holding traditional gender attitudes would increase women's chances of becoming office clerks. In contrast, those tending to be more progressive are more likely to become managers.